Decision making and knowledge decision support systems : VIII International Conference of RACEF, Barcelona, Spain, November 2013 and International Conference MS 2013, Chania Crete, Greece, November 2013 /: VIII International Conference of RACEF, Barcelona, Spain, November 2013 and International Conference MS 2013, Chania Crete, Greece, November 2013. (2014) - Unknown
No abstract available